The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1029/2019je006276
|View full text |Cite
|
Sign up to set email alerts
|

Venusian Habitable Climate Scenarios: Modeling Venus Through Time and Applications to Slowly Rotating Venus‐Like Exoplanets

Abstract: One popular view of Venus' climate history describes a world that has spent much of its life with surface liquid water, plate tectonics, and a stable temperate climate. Part of the basis for this optimistic scenario is the high deuterium to hydrogen ratio from the Pioneer Venus mission that was interpreted to imply Venus had a shallow ocean's worth of water throughout much of its history. Another view is that Venus had a long-lived (∼100 million years) primordial magma ocean with a CO 2 and steam atmosphere. V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 297 publications
(533 reference statements)
3
109
0
Order By: Relevance
“…With the host star being similar to the Sun, the known HD136352 planets lie far interior to the inner boundaries of the Habitable Zone (Kasting et al 1993;Kopparapu et al 2013Kopparapu et al , 2014Kane et al 2016a), but they do lie within the Venus Zone . This is mostly relevant to planet b and other terrestrial planets that may be present within the system, because the exploration of planetary habitability and comparative planetology aims to study the major factors that drive the bifurcation of habitable versus uninhabitable environments (Hamano et al 2013;Kane et al 2019;Way & Del Genio 2020). Terrestrial planets orbiting close to a bright host star, such as those discussed here, provide the best opportunities to conduct the needed atmospheric studies to inform the diversification processes (Ostberg & Kane 2019).…”
Section: Exoplanet Demographicsmentioning
confidence: 99%
“…With the host star being similar to the Sun, the known HD136352 planets lie far interior to the inner boundaries of the Habitable Zone (Kasting et al 1993;Kopparapu et al 2013Kopparapu et al , 2014Kane et al 2016a), but they do lie within the Venus Zone . This is mostly relevant to planet b and other terrestrial planets that may be present within the system, because the exploration of planetary habitability and comparative planetology aims to study the major factors that drive the bifurcation of habitable versus uninhabitable environments (Hamano et al 2013;Kane et al 2019;Way & Del Genio 2020). Terrestrial planets orbiting close to a bright host star, such as those discussed here, provide the best opportunities to conduct the needed atmospheric studies to inform the diversification processes (Ostberg & Kane 2019).…”
Section: Exoplanet Demographicsmentioning
confidence: 99%
“…However, dynamical studies have shown that the different terrestrial planets likely received different amounts of material from different reservoirs of volatiles-at least in the case of the exogenous delivery of those volatiles (e.g., ; T. Owen & Bar-Nun, 1996; Raymond et al, 2004), a result that has been replicated in studies of planet formation around other stars (e.g., Ciesla et al, 2015). This finding has implications, for example, for the volatile inventory of Venus and its similarity (or not) with that of Earth (e.g., Way & Del Genio, 2020).…”
Section: Earthmentioning
confidence: 92%
“…6. Did Venus have a habitable period (Way & Del Genio, 2020;Way et al, 2016)? That is, did Venus ever cool after formation (Hamano et al, 2013)?…”
Section: Venusmentioning
confidence: 99%
See 1 more Smart Citation
“…The leading theory on Venus' climatic history is that it left surface habitability early in its history during a runaway greenhouse period [120][121][122]. However, some recent climate models suggest that Venus may have harbored liquid water on its surface for up to three billion years after the formation of the Solar System [123,124]. In these scenarios, the onset of a strong greenhouse effect was delayed by Venus' slow rotational period [123].…”
Section: Venusmentioning
confidence: 99%